2018
DOI: 10.15517/rbt.v66i1.33297
|View full text |Cite
|
Sign up to set email alerts
|

Water parameters and primary productivity at four marine embayments of Costa Rica (2000-2002)

Abstract: The availability of baseline data on water parameters and primary productivity is essential in comparative studies aimed at identifying environmental trends, like eutrophication, in coastal embayments. In this context, the objetive of this work is to make accessible data, collected from 2000 to 2002, on 13 water parameters (Secchi depth, temperature, salinity, dissolved oxygen, oxygen saturation, suspended matter, chlorophyll-a, phaeopigments, phosphate, silicate, ammonium, nitrite and nitrate) their temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 14 publications
2
5
2
7
Order By: Relevance
“…Additionally, the statistical analysis showed no significant differences between the seasons (n = 103, p > 0.05). The values found in this study are similar to those reported by Muller-Parker and Cortés [34] for the northern Pacific area of Costa Rica (28 • C), by Alfaro et al [12] (range between 24.85 ± 1.63 and 29.26 ± 0.51 • C, for the months of February-March and August) and by Vargas-Zamora et al [35] (between 24.0 and 32.5 • C, with an average of 28.7 ± 0.6 • C), both for Culebra Bay. It is important to remember that the Papagayo Gulf is influenced by coastal currents, coastal upwelling, and local and synoptic wind patterns.…”
Section: Temperature Salinity and Dissolved Oxygen Profilesupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the statistical analysis showed no significant differences between the seasons (n = 103, p > 0.05). The values found in this study are similar to those reported by Muller-Parker and Cortés [34] for the northern Pacific area of Costa Rica (28 • C), by Alfaro et al [12] (range between 24.85 ± 1.63 and 29.26 ± 0.51 • C, for the months of February-March and August) and by Vargas-Zamora et al [35] (between 24.0 and 32.5 • C, with an average of 28.7 ± 0.6 • C), both for Culebra Bay. It is important to remember that the Papagayo Gulf is influenced by coastal currents, coastal upwelling, and local and synoptic wind patterns.…”
Section: Temperature Salinity and Dissolved Oxygen Profilesupporting
confidence: 92%
“…It must be taken into consideration that the concentration of this parameter depends not only on temperature but also on salinity, although there are natural conditions that could have a greater influence on its concentration, such as primary productivity and the degradation of organic matter [11]. For this study in the Gulf of Papagayo, the dissolved oxygen concentration was slightly higher than that reported by Vargas-Zamora et al [35] for Culebra Bay (5.16-8.20 mg L −1 ). This discrepancy may be due to the fact that in some months of the dry season, there were strong winds where the variation was between 59 and 92 km h −1 .…”
Section: Temperature Salinity and Dissolved Oxygen Profilementioning
confidence: 52%
See 2 more Smart Citations
“…Entre los posibles cambios en el funcionamiento del Golfo de Nicoya, hay evidencia de que el estuario ha superado los valores de productividad primaria asociados a condiciones eutróficas (Cloern, Foster, & Klechner 2014). Saturaciones de oxígeno superiores al 100 %, como la encontrada en la estación 06 del V. Hensen, además de concentraciones altas de clorofila-a y estimaciones de productividad primaria neta superiores a 500 g C /m 2 / año han sido documentadas en aguas superficiales del Golfo (Vargas-Zamora et al, 2018). Tal como lo ha indicado Jackson et al (2001) la extracción de organismos que se alimentan de fitoplancton (como los moluscos bivalvos y algunos peces) ha contribuido a la eutroficación en algunos estuarios en otras latitudes.…”
Section: Discussionunclassified